Fibonacci, Lucas, and a Game of Chance. Issue 5 (1st December 2016) - Torrence, Bruce; Torrence, Robert
Summary: A simple game of chance is introduced, where it is shown that each player's winning probability is a ratio of Fibonacci and Lucas numbers.